A Rab5 endosomal pathway mediates Parkin-dependent mitochondrial clearance - Babette C. Hammerling (Nature Portfolio, 2017)
Damaged mitochondria are normally cleared through canonical and alternative autophagy pathways. Here, the authors report that mitochondria can be cleared through an autophagy-independent endosomal-lysosomal pathway that depends on Parkin-dependent sequestration of mitochondria in Rab5-positive early endosomes.